2022
DOI: 10.3390/ijms23073518
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Potential Use of Chemical Biopsy Devices to Characterize Brain Tumor Lipidomes

Abstract: The development of a fast and accurate intraoperative method that enables the differentiation and stratification of cancerous lesions is still a challenging problem in laboratory medicine. Therefore, it is important to find and optimize a simple and effective analytical method of enabling the selection of distinctive metabolites. This study aims to assess the usefulness of solid-phase microextraction (SPME) probes as a sampling method for the lipidomic analysis of brain tumors. To this end, SPME was applied to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…1 , a mixture of MetOH/IPA (50:50, v/v ) and also a mixture of MetOH/IPA (25/75, v/v ) with addition of ammonium acetate and acidic acid presented the best recoveries among evaluated solvents for each analyte. Ultimately, a mixture MetOH/IPA (50:50, v/v ) was selected for further analysis on ECs, which is in agreement with previous observations during the analysis of 2-AG and AEA analyzed in plasma samples (Acquaro Junior et al, 2019 ), and this mixture is also the most feasible during untargeted lipidomics studies (Bogusiewicz et al, 2021 , 2022 ). In addition, the use of MetOH/IPA (50:50, v/v) mixture provided a carryover values lower than 2% for all compounds, which indicated that majority of extracted analytes were desorbed into the selected desorption mixture.…”
Section: Resultssupporting
confidence: 79%
“…1 , a mixture of MetOH/IPA (50:50, v/v ) and also a mixture of MetOH/IPA (25/75, v/v ) with addition of ammonium acetate and acidic acid presented the best recoveries among evaluated solvents for each analyte. Ultimately, a mixture MetOH/IPA (50:50, v/v ) was selected for further analysis on ECs, which is in agreement with previous observations during the analysis of 2-AG and AEA analyzed in plasma samples (Acquaro Junior et al, 2019 ), and this mixture is also the most feasible during untargeted lipidomics studies (Bogusiewicz et al, 2021 , 2022 ). In addition, the use of MetOH/IPA (50:50, v/v) mixture provided a carryover values lower than 2% for all compounds, which indicated that majority of extracted analytes were desorbed into the selected desorption mixture.…”
Section: Resultssupporting
confidence: 79%
“…Although the relative concentration obtained from the intact tissue corresponded to the concentration measured in the homogenate (calculated based on the standard addition method), several issues should be discussed prior to further attempts to develop the calibration strategy to determine endogenous compounds in cancer tissue with CBS-MS. First, since brain tumors are characterized by high heterogeneity, the homogenization of a small section may only result in the selection of a portion of the tumor’s phenotype [ 22 ]. Conversely, SPME probes enable the extraction of analytes along the sorbent from various parts of the tumor [ 30 ]. Second, the CBS-MS device has a bigger extraction surface than SPME fibers, which means that it can be influenced more easily by the composition of a changed region (e.g., the calcified part of the tumor where extraction is altered at a specific part of the blade).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the fibers were desorbed into 150µl of isopropanol: methanol (1:1 v/v) solution using silanized inserts. Desorption was conducted for 1 hour under agitation at 850 rpm [12]. Pooled quality control (QC) and extraction blanks were also prepared [12].…”
Section: Chemical Biopsy (Solid-phase Microextraction) Protocol and L...mentioning
confidence: 99%
“…Desorption was conducted for 1 hour under agitation at 850 rpm [12]. Pooled quality control (QC) and extraction blanks were also prepared [12].…”
Section: Chemical Biopsy (Solid-phase Microextraction) Protocol and L...mentioning
confidence: 99%